Smart Buff Manager: A Co-Designed Mobile Application for Enhancing Buffalo Farm Management in Thailand - Saengwong, Sureeporn; Kongmuang, Nattamaporn; Intawicha, Payungsuk; Tiantong, Attapol; Inyawilert, Wilasinee (Journal of Buffalo Science, 2024)
This study focuses on the co-design and development of a smartphone application, the "Smart Buff Manager," especially for smallholder buffalo farmers in Thailand. The application aims to meet the needs of buffalo farmers by providing an effective and user-friendly tool for record-keeping and farm management. We employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design method to ensure the application addressed the practical needs and preferences of the farmers. The primary features of the app include record-keeping, health monitoring, and breeding management, focusing on various issues faced by smallholder farmers. The user-centered design method provides an intuitive interface that gathers feedback from users, resulting in increased satisfaction and a higher tendency to recommend apps. Implementation of the app significantly improved farm management by enhancing operational efficiency, productivity, and animal welfare. Users of the application reported much greater compliance with vaccination schedules than non-users, potentially improving herd health and long-term production. This case study confirms the potential of mobile technology to improve farm operations and decision-making while also highlighting the essential role of involving end-users in the design process to develop appropriate and effective digital farming systems.